PENGARUH EKSPOR DAN IMPOR TERHADAP PERTUMBUHAN EKONOMI INDONESIA PERIODE 2014-2023 - Khoirul Thoha, Ahmad; Restikasari, Wenny (Jurnal Ekonomika : INDEPENDEN, 2024)
Increased economic growth is influenced by increased exports and imports, especially in the era of globalization. However, there are trade policies that can harm the national economy. Therefore, this research aims to determine the influence of exports and imports on Indonesia's economic growth for the 2014-2023 period. This research uses a quantitative approach with annual time series data taken using documentation techniques. In addition, multiple linear regression analysis techniques were used in this research to see the influence of export and import variables on Indonesia's economic growth. The results of this research are that exports have a significant negative effect on Indonesia's economic growth. Meanwhile, imports influence Indonesia's economic growth in a significantly positive way.